"Majority‐Rules" Effect on Supramolecular Chirality and Optoelectronic Properties of Chiral Tetrachloro‐Perylene Diimides. Issue 6 (28th December 2020) - Shang, Xiaobo; Song, Inho; Han, Myeonggeun; Lee, Jeong Hyeon; Ohtsu, Hiroyoshi; Choi, Wanuk; Kim, Jin Chul; Ahn, Jaeyong; Kwak, Sang Kyu; Oh, Joon Hak
Abstract: Supramolecular chirality has attracted a great deal of attention as a platform for both fundamental study and chirality amplification in various research fields. Compared with the "sergeants‐and‐soldiers" principle, the "majority‐rules" principle, which affects chirality amplification in supramolecular systems, is rarely reported for nano/microstructures. Here, chiral tetrachloro‐substituted perylene diimides are synthesized that self‐assemble into chiral supramolecules with different degrees of enantiomeric excess (ee). Interestingly, it is found that quasi‐2D crystals are gradually transferred to 1D nanowires (NWs) with ee from 100% to 0%. In the racemic system, chiral self‐discrimination is observed due to the greater thermodynamic stability of heterochiral crystals than the homochiral counterparts, judging from the theoretical studies. Circular dichroism analysis indicates that the self‐assembled system with different ee values shows different peaks due to their unique molecular ordering for supramolecular exciton coupling. On measurement in optoelectronic devices, racemic 1D NWs show better charge transport ability than enantiomeric quasi‐2D crystals. These results provide guidelines for tuning the supramolecular chirality and optoelectronic performance of self‐assembled systems via the "majority‐rules" principle. Abstract : Chiral supramolecules with different enantiomeric excess (ee) are self‐assembled into quasi‐2D single crystals with different morphologies. The quasi‐2D crystals are gradually transformed to nanowires (NWs) with ee from 100% to 0%. The racemic NWs show better charge transport than enantiomeric quasi‐2D crystals. These results provide guidelines for tuning supramolecular chirality and optoelectronic performance of self‐assembled systems via the "majority‐rules" principle.